Analysis of the Moral Value Found in Hamlet Based on Its Intrinsic Value - Elisa Ismitasari (International Journal of English Language and Pedagogy, 2023)
The potential teacher must study the broad subject, the subject of expertise, and the professional subject. Additionally, one of the proficiency courses is literature. The goal of this study, "Analysis of Moral Value Found in Hamlet Based on Its Intrinsic Value," was to identify the many kinds of moral values and intrinsic values that are conveyed in the film as well as the moral values that recur frequently. The qualitative research method was employed in this study. The research instrument was a collection of questions based on the intrinsic value expressed in the movie script. To find the forms of moral values, the data was gathered by downloading the movie's screenplay from the internet. The writer concentrated on the intrinsic value components and different moral ideals when examining the screenplay. The study of the data revealed: 1) topic; 2) character and characterization; 3) setting; 4) plot; 5) suspense and foreshadowing; 6) dialogue; 7) audience; 8) actors and actresses; 9) stage director, are aspects of intrinsic value. A data study revealed that the following moral ideals are presented in the film "Hamlet": 1) reverence: to be respectful; 2) faithfulness: to be loyal and persistent; 3) awareness of responsibility: to be responsible, trustworthy, and reliable; 4) veracity: to be honest, truthful, and humble; and 5) goodness: to be affectionate, kind, and loving. In the "Hamlet" movie, reverence is a common example of a moral value.